Initiation of apremilast treatment decreases prescribed topical therapy amount in patients with psoriasis: a health insurance claims study in Japan - Siddharth Chaudhari; Ryuichi Ogawa; Shinichi Imafuku; Hiroshi Saruwatari; Katarzyna Jabłońska; Kathy Tran (Journal of Dermatological Treatment)
Objective Effective systemic treatments for psoriasis may reduce the need for topical therapies. The objective of this study was to evaluate changes in topical prescriptions after apremilast initiation.Materials and methods This retrospective cohort study was performed in the Japanese JMDC health insurance claims database. Adults with psoriasis initiating apremilast between 01/03/2018 and 31/07/2021 and prescribed topical therapies in the previous six months were eligible. Topical therapy prescription was compared between the six months preceding and the six months following apremilast initiation. Data from 319 patients were analyzed.Results The cumulative amount (grams) of topical therapies prescribed decreased significantly following apremilast initiation from 195.8 ± 236.1 to 162.2 ± 230.9 for steroids (p < 0.001) and from 84.6 ± 89.6 to 77.1 ± 104.6 for vitamin D analogues (p = 0.018). No significant change was observed for fixed-dose combinations (from 133.2 ± 140.0 to 143.4 ± 136.8; p = 0.487) or total topical therapy (from 309.9 ± 272.3 to 301.0 ± 293.0; p = 0.131). For steroids, the reduction was only significant for ‘very strong’ potency steroids (-33.6 g; p = 0.001). Eighteen patients (6%) discontinued all topical therapy following apremilast initiation and 69 (22%) were prescribed fewer concomitant topical therapies.Conclusion In conclusion, initiation of systemic apremilast treatment is associated with reduced prescription of topical therapies. Treatment with apremilast may decrease the burden of long-term exposure to topical therapies.